2020
DOI: 10.1101/2020.06.12.148320
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Immunoresolvents Support Skeletal Myofiber Regeneration via Actions on Myeloid and Muscle Stem Cells

Abstract: 150-word limit):Specialized pro-resolving mediators (SPMs) actively limit inflammation and expedite its resolution. Here we profiled intramuscular lipid mediators following injury and investigated the role of SPMs in skeletal muscle inflammation and repair. Both eicosanoids and SPMs increased following myofiber damage induced by intramuscular injection of barium chloride or functional overload. Daily systemic administration of resolvin D1 (RvD1) limited the degree and duration of inflammation, enhanced regener… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
15
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(22 citation statements)
references
References 114 publications
5
15
2
Order By: Relevance
“…Treatment of aged mice with the prototypical SPM, RvD1, at the time of injury suppressed muscle expression of both pro-and anti-inflammatory cytokines including MCP-1, IL-1β, and IL-10. Despite this, unlike our prior study in young mice (Markworth et al, 2020), in the present study we were unable to demonstrate in aged mice a reduction in MΦ infiltration of muscle in response to RvD1 treatment. Moreover, other inflammationrelated genes (e.g.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Treatment of aged mice with the prototypical SPM, RvD1, at the time of injury suppressed muscle expression of both pro-and anti-inflammatory cytokines including MCP-1, IL-1β, and IL-10. Despite this, unlike our prior study in young mice (Markworth et al, 2020), in the present study we were unable to demonstrate in aged mice a reduction in MΦ infiltration of muscle in response to RvD1 treatment. Moreover, other inflammationrelated genes (e.g.…”
Section: Discussioncontrasting
confidence: 99%
“…The ability of systemic RvD1 administration to limit PMN recruitment is well-described for certain experimental models of acute inflammation (Norling, Dalli, Flower, Serhan, & Perretti, 2012). In contrast, we have been unable to demonstrate this in the context of sterile skeletal muscle injury in either young (Markworth et al, 2020), or old mice (present study). Prior studies in cardiac muscle found that systemic injection of RvD1 was also unable to limit PMN appearance following myocardial infarction (Halade, Kain, & Serhan, 2018;Kain et al, 2015).…”
Section: Spms Hepes Hdohes)contrasting
confidence: 67%
See 3 more Smart Citations